Determination of Salmonella spp. and quantification of shell changes and internal content of eggs sold in Natal and Mossoró, Rio Grande do Norte (Research, Society and Development, 2020)
This research sought to identify the presence of Salmonella spp. and quantify changes in the shell and internal content of eggs sold in Mossoró and Natal, the two most populous cities in the state of Rio Grande do Norte. For the evaluation of changes in shell and internal content, 360 eggs were individually analyzed by the following parameters: egg weight; presence of dirt; presence of cracks in the shell; measurements in the air chamber; yolk integrity; presence of changes in the albumen and / or presence of blood. For the microbiological analysis of the skin and internal content, the presence of Salmonella spp. Was evaluated by conventional methods. Blood stains were found in 15% of the whites, 33% of the buds and lack of integrity in 28.3% of the buds. Changes in the integrity of the shells were found, in which 10% were broken, 40% cracked and 90% dirty. The height of the air chamber in 76.6% of the evaluated eggs varied by more than 6 mm and 13.33% of the eggs were in disagreement with the legislation regarding typification. The bacterium Salmonella spp. was isolated in 4.17% of the samples, 2.5% in the bark and 1.67% in the yolk. Poor internal and external quality was evidenced in a considerable number of eggs sold in the municipalities of Mossoró and Natal - RN, emphasizing the need for more effective inspection by Organs federal, state and municipal agencies involved with the surveillance and inspection of this product. In addition, it is necessary to establish stricter measures to ensure consumer health.